Catastrophic Health Expenditure and Household Impoverishment: a case of NCDs prevalence in Kenya - Daniel Mwai; Moses Muriithi (Epidemiology, Biostatistics and Public Health)
Introduction and problem: Non-Communicable Diseases (NCDs) have become one of the leading causes of morbidity and mortality in Kenya. Their claim on financial and time resources adversely affects household welfare. Health care cost for NCDs in Kenya is predominantly paid by households as OOP. Health expenditure on NCD stands at 6.2% of Total Health Expenditure which is 0.4 % of the total gross domestic product of the country. This expenditure scenario could have implications on household welfare through catastrophic expenditure in Kenya. Most studies done on catastrophic expenditure in Kenya have not looked at the effect of NCD on poverty. Methodology: The paper has investigated the determinants of catastrophic health spending in a household with special focus on the NCDs. It has also investigated the effect of catastrophic expenditure on household welfare.A National household level survey data on expenditure and utilization is used. Controlling for endogeneity, the results revealed that NCDs and communicable diseases contribute significantly to the likelihood of a household incurring catastrophic expenditure. Results: Although all types of sicknesses have negative effects on household welfare, NCDs have more severe impacts on impoverishment. Policy wise, government and development partners should put in place a health financing plan entailing health insurance and resource pooling as a mean towards social protection. Key words:  Non-Communicable Diseases (NCD), Catastrophic Health Expenditure, endogeneity Impoverishment